The Influence of Internal Factors and Customer Relations on the Success of Big Data and AI Projects with Moderating Government Regulations at PT. Dua Empat Tujuh - Bagus Rully Muttaqien; Slamet Ahmadi (GoodWill, 2025)
This study aims to evaluate the effectiveness of government regulations in supporting product innovation strategies, human resource management, and data protection in the context of digital transformation based on artificial intelligence (AI) and big data technology. This study was conducted using a literature study approach, referring to various academic sources including strategic management textbooks, innovation, marketing, and the latest journal articles that discuss the relationship between government policies and organizational performance. The results of the study indicate that government regulations can provide constructive direction and limitations on the application of technology, but also have the potential to hinder organizational agility if not balanced with adaptive strategies. In this context, the company's ability to manage human resources, build ethical customer relationships, and encourage innovation that complies with regulations is the key to success. This study emphasizes the importance of integration between regulatory compliance and strategic flexibility in developing sustainable and competitive business models in the digital era.